EARLY WHOLE BODY VERSUS FOCUSED COMPUTED TOMOGRAPHY IMAGING FOLLOWING MAJOR TRAUMA: EXISTING EVIDENCE AND ANALYSIS OF 10 YEARS OF TARN DATA. Issue 12 (23rd November 2015) - Hunt, P; Bouamra, O; Jenks, T; Lecky, FE; Edwards, A; Woodford, M; Yates, D; Han, K
Abstract : Objectives & Background: Whole Body Computed Tomography (WBCT) scanning is considered to be the chief imaging modality for patients with major trauma. There is growing evidence that the rate of survival is higher for patients undergoing early WBCT by facilitating rapid and accurate anatomical characterisation of potentially life-threatening injuries. There remains ongoing controversy whether this outweighs the potential risks from high-dose ionising radiation. Methods: Data from the Trauma Audit and Research Network (TARN) trauma registry was analysed for all patients presenting from January 2005 to July 2014 inclusive aged 16 years or more admitted directly to hospital Emergency Departments (ED) with suspected severe blunt polytrauma. Survival was compared between two groups: (1) patients who underwent WBCT scans, and (2) those who underwent a focused CT ("non-WBCT") scanning approach within the first four hours of arrival at the ED. Results: 14, 598 (23·2%) of 62, 942 eligible cases underwent WBCT directly from the ED within four hours of arrival. The calculated crude survival rate for the WBCT group was 89·2%, compared to 88·9% in the non-WBCT group (p=0·260). The results of multivariate regression analysis, taking account of all possible confounders, demonstrated a trend towards improved survival in the WBCT scan group, with an OR=1·080 (95% CI 0·986–1·183) compared to the non-WBCT group (p=0·098). Conclusion: The results of our investigation demonstrate a trend towards improved survival for adult patients with suspected severe blunt polytrauma undergoing WBCT scanning early in their management in the ED. Our analysis of the largest series of trauma cases investigating WBCT so far is the first to take account of all possible confounding factors including centre effect – often a major limitation for generalisability in previous studies of this kind. The existing evidence for the use of WBCT during the management of major trauma is also discussed in the context of these new resultsFigure 1 Figure 2 .